Resistência ao esforço cortante no concreto leve - Castro, Newton de (1971)
The scope of the present paper is the study of the shear strength of structural members made of lightweight concrete. Ten lightweight reinforced concrete beams prepared with expanded shale coarse aggregates were tested. The beams were designed in such way that their geometrical and mechanical characteristics were different for each specimen. The set of beams tested were arranged in two different groups regarding the colapse behavior, namely: a) crushing of the concrete web in the direction of the diagonal cracks; b) yield of the web reinforcement. The dependence of the ammount of the shear force supported only by the concrete on the ratio M/Th was investigated. The test results have shown that the specifications suggested by the "Comité Européen du Béton - Fédération Internationale de la Pré-contrainte", for evaluating the allowable shear strength of structural members can also be used for lightweigth reinforced concrete beams.